2009
DOI: 10.1167/iovs.08-3147
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Gelatinase (MMP-2 and MMP-9) in Pterygia and Pterygium Fibroblasts with Disease Progression and Activation of Protein Kinase C

Abstract: MMP-2 and MMP-9 expression by pterygium fibroblasts is significantly increased after the progression of pterygium. Activation of the PKC signaling pathway, aside from other previously reported signaling pathways, may play a role in the development and progression of pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 34 publications
3
52
0
2
Order By: Relevance
“…Ocular dryness has therefore been proposed as a risk factor for pterygium and pterygium recurrence by triggering the secretion of potent proinflammatory cytokines and increasing the expression of MMPs by conjunctival epithelial cells [20] and pterygium body fibroblasts [21]. Indeed, levels of MMP-9 -the most important gelatinase on the ocular surface -are significantly elevated in DED [20] and have also been shown to correlate with pterygium formation and progression [22]. Importantly, VanDerMeid et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular dryness has therefore been proposed as a risk factor for pterygium and pterygium recurrence by triggering the secretion of potent proinflammatory cytokines and increasing the expression of MMPs by conjunctival epithelial cells [20] and pterygium body fibroblasts [21]. Indeed, levels of MMP-9 -the most important gelatinase on the ocular surface -are significantly elevated in DED [20] and have also been shown to correlate with pterygium formation and progression [22]. Importantly, VanDerMeid et.al.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that pterygium head Wbroblasts had higher expression and active MMP-1 and MMP-3 (Li et al 2001). All these MMPs (1, 2, 3 and 9) would then work synergistically to degrade the Bowman's membrane and ECM (Yang et al 2009). The invasion capacity was also regulated by their interaction with TIMPs (Tsai et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the MMP-2 and MMP-9 expression levels in pterygium tissues and fibroblasts were higher than those of normal tissues and fibroblasts and closely relevant to the progression of pterygium. Also, in early-stage pterygium tissues and cultured fibroblasts, MMP-2 or MMP-9 was at low or undetectable levels, while in advanced-stage pterygium (pterygium head passed the papillary region), MMP-2 and MMP-9 could be obviously detected in pterygium tissues and fibroblasts (16). In addition, down-regulation of the expression levels of MMP-3 and MMP-13 was capable of suppression of the proliferation and migration of pterygium fibroblasts (24,25).…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that MMP-1 and MMP-3, but not MMP-2, TIMP-1, TIMP-2 or uPA, were highly expressed in pterygium head, body and subconjunctival fibroblasts (14). Although Schellini and his colleagues demonstrated that the expression of MMP-9 was similar among the tissues from normal Tenon's capsule and primary or recurrent pterygia (15), Yang has oppositely proposed that the expression of MMP-9 by pterygium fibroblasts is significantly increased after the progression of pterygium (16). One of the reasons to explain the inconsistency is that the clinical sample sizes in the two researchers were only 6 and 15, respectively.…”
mentioning
confidence: 99%